Digital Marginalization in Talang Kemuning Village: The Impact of Internet Access Inequality on Social Life - Maharani, Tuti; Azwar, Welhendri; Jamil, Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study investigates the phenomenon of digital marginalization in Talang Kemuning Village, where inadequate network infrastructure creates significant barriers to digital inclusion. Grounded in Amartya Sen's Capability Approach, the research conceptualizes development as a process of expanding individuals' substantive freedoms to achieve valued ways of living. The absence of reliable internet access has created multidimensional deprivation, limiting residents' ability to participate in digital communication, access vital information, and engage in socioeconomic opportunities. The study addresses two central questions: (1) How does infrastructure deficiency perpetuate digital inequality in rural communities? (2) What strategies can local change agents employ to mitigate these disparities? Using a qualitative descriptive methodology, we analyze geographical constraints, technical limitations, and the resultant social exclusion. Data collection included in-depth interviews with community members and participatory observation of digital access initiatives. Findings reveal that connectivity limitations create cascading effects: students face educational disadvantages due to inability to access online learning; local entrepreneurs are excluded from digital marketplaces; and social isolation intensifies as community members cannot participate in virtual networks. However, the research documents an innovative community-led solution through the implementation of a voucher-based WiFi system. This intervention demonstrates how localized approaches can simultaneously address technical access barriers while enhancing human capabilities. The study contributes to digital development literature by showing how Sen's framework applies to connectivity challenges. It argues that sustainable solutions require both technological infrastructure and capacity-building initiatives that empower communities to convert access into meaningful opportunities. These insights have important implications for policymakers designing inclusive digital development programs in rural contexts.